Memory CD4 T Cells Induce Antibody-Mediated Rejection of Renal Allografts - Gorbacheva, Victoria (J Am Soc Nephrol, 2016)
Despite advances in immunosuppression, antibody-mediated rejection is a serious threat to allograft survival. Alloreactive memory helper T cells can induce potent alloantibody responses and often associate with poor graft outcome. Nevertheless, the ability of memory T cells to elicit well characterized manifestations of antibody-mediated rejection has not been tested. We investigated helper functions of memory CD4 T cells in a mouse model of renal transplantation. Whereas the majority of unsensitized C57Bl/6 recipients spontaneously accepted fully MHC–mismatched A/J renal allografts, recipients containing donor–reactive memory CD4 T cells rapidly lost allograft function. Increased serum creatinine levels, high serum titers of donor-specific alloantibody, minimal T cell infiltration, and intense C4d deposition in the grafts of sensitized recipients fulfilled all diagnostic criteria for acute renal antibody–mediated rejection in humans. IFNγ neutralization did not prevent the renal allograft rejection induced by memory helper T cells, and CD8 T cell depletion at the time of transplantation or depletion of both CD4 and CD8 T cells also did not prevent the renal allograft rejection induced by memory helper T cells starting at day 4 after transplantation. However, B cell depletion inhibited alloantibody generation and significantly extended allograft survival, indicating that donor-specific alloantibodies (not T cells) were the critical effector mechanism of renal allograft rejection induced by memory CD4 T cells. Our studies provide direct evidence that recipient T cell sensitization may result in antibody-mediated rejection of renal allografts and introduce a physiologically relevant animal model with which to investigate mechanisms of antibody-mediated rejection and novel therapeutic approaches for its prevention and treatment.